Peningkatan Keterampilan Menulis Cerpen dengan Menggunakan Model Problem Based Learning pada Peserta didik Kelas IX - Nina Prince Simorangkir (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Learning literature, especially writing short stories, should take as much time as possible because students can immediately feel the function of literature, especially short stories. Therefore, the approach to teaching literature, and especially short stories, needs to be creative rather than rote. It should inspire students to write, reflect, and experience problems in the light of short story principles. The aim of the research is to determine the improvement in short story writing skills of class IX students by using a problem-based approach (Problem Based Learning). This research method uses experiments, with two data collection methods, namely test and non-test techniques. Using the PBL methodology, the written test form is filled in by completing a short story writing practice exam. Meanwhile, observation sheets, teacher and student notebooks, interview sheets, and video recordings were used to collect non-test data. Based on the results of this research, it is understood that before treatment (without the PBL learning paradigm), the students' average score was 48.16 with a standard deviation of 7.00. There are 8 students in the sufficient group, or 26.66%, 20 students in the poor category, or 66.66%, and 2 students in the very poor category, or 6.66%. The average post-test score was 78, with a standard deviation of 7.48. Nine students, or 30%, were in the very good group, 18 students, or 60%, were in the good category, and 3 students, or 10%, were in the fair category.